2009
DOI: 10.1016/j.mce.2008.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The GK rat beta-cell: A prototype for the diseased human beta-cell in type 2 diabetes?

Abstract: Increasing evidence indicates that decreased functional beta-cell mass is the hallmark of type 2 diabetes (T2D) mellitus. Nowadays, the debate focuses on the possible mechanisms responsible for abnormal islet microenvironment, decreased beta-cell number, impaired beta-cell function, and their multifactorial aetiologies. This review is aimed to illustrate to what extend the Goto-Kakizaki rat, one of the best characterized animal models of spontaneous T2D, has proved be a valuable tool offering sufficient common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 141 publications
(209 reference statements)
7
110
0
2
Order By: Relevance
“…Commonalities in b-cell dysfunction regarding human type 2 diabetes and GK rats include reduction in b-cell mass, alterations in islets microenvironment, and multiple functional deficits (Seiça et al 2004, Portha et al 2009). As expected, GK rats in this study showed impaired metabolic control in comparison with Wistar rats, with significantly worse HbA1c levels and higher blood glucose levels, 2 h after an OGTT, both at the beginning and at the end of the observation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonalities in b-cell dysfunction regarding human type 2 diabetes and GK rats include reduction in b-cell mass, alterations in islets microenvironment, and multiple functional deficits (Seiça et al 2004, Portha et al 2009). As expected, GK rats in this study showed impaired metabolic control in comparison with Wistar rats, with significantly worse HbA1c levels and higher blood glucose levels, 2 h after an OGTT, both at the beginning and at the end of the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the effect of surgery on glucagon metabolism and its influence on outcome regarding remission of diabetes. Goto-Kakizaki (GK) rats have been studied extensively as a model for type 2 diabetes in non-obese humans, and display similar features in comparison with the human pancreatic phenotype in patients with type 2 diabetes (Seiça et al 2003, Portha et al 2009). Thus, we studied the effect of common bariatric procedures such as sleeve gastrectomy and gastric bypass on glucose metabolism, insulin sensitivity, and pancreatic hormone secretion in this rodent model.…”
Section: Introductionmentioning
confidence: 99%
“…We did, however, find a notable reduction in ir NUCB2 in islet homogenates obtained from the GK rats, which normalized with fasting (present results). The inbred non-obese GK rats recapitulate several of the salient features of b-cell pathology in T2DM, including impaired insulin secretion and glucose intolerance (Ö stenson & Efendic 2007, Portha et al 2009). (Of note, in the Stockholm GK colony used in this study, no reduction in b-cell mass is detected at three months, which is the maximum age for animals included in the present study; Guenifi et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We have also performed the first investigation of the relationship between pancreatic NUCB2 and metabolic state. Thus, we investigated the levels of NUCB2 in serum and pancreatic islets under different metabolic conditions, including food restriction, and in the Goto-Kakizaki (GK) rats, model of type 2 diabetes mellitus (T2DM; Goto et al 1975, Ö stenson & Efendic 2007, Portha et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…We have found that ciliary/basal body defects lead to pre-diabetic phenotypes in vitro and in vivo, but to establish a link between primary cilia and diabetes, we tested for ciliary dysfunction in diabetic GotoKakizaki (GK) rats 50,51 . GK rats from the Stockholm colony manifest a marked glucose intolerance with hyperglycemia, mainly due to impaired glucose-stimulated insulin secretion.…”
Section: Disruption Of Basal Body Integrity Impairs Insulin Secretionmentioning
confidence: 99%